A indústria editorial em Galiza - Verdugo Matés, Rosa María (1998)
"The object of this Doctoral Thesis is to analyse the evolution of the Galician publishing industry during the period 1973-1996. It being understood that industry means, in the first instance, the total number of publishers who have their headquarters within the political-administrative territory of Galicia and in the second, the publishers with headquarters outside this geographical area, who have published titles in the Galician language during this same period of time. The analysis begins with the characterisation of the object of study, the published book, highlighting its importance from the cultural and economic point of view. In a later phase, using the TIO-90 of Galicia, the publishing industry is situated within the framework of the Galician economy as a whole and a study is made of the existing relationships between this sector and the rest of the economic sectors. The investigation is centred on the study of the offer, distribution and sale of books written in the Galician language and this area constitutes the main part of the paper. With regard to offer, after first analysing the temporal evolution of the variables that influence the production of books, a study is made of the editorial offer in the different languages and historical nationalities of the Spanish political sphere. Simultaneously, an examination is made of how available resources are allocated in the Galician, Catalan, Basque and Castilian languages. With regard to distribution, apart from analysing the importance of the different channels of distribution and sale, the existing controversy regarding the consequences to be expected from eventual changes in the policy of price regulation is discussed. In a similar manner to the section on offer, the section on procurement studies the temporal evolution of the variables that define the function of editorial demand. To finalise, the results of a study carried out in a sample of Galician schools in the 1995-96 school year are shown. These results make it possible to quantify the sales volume of school texts in the Galician language and identify the publishers who participated in these sales."